Homologous Recombination and Translesion DNA Synthesis Play Critical Roles on Tolerating DNA Damage Caused by Trace Levels of Hexavalent Chromium. - Xu Tian; Keyur Patel; John R Ridpath; Youjun Chen; Yi-Hui Zhou; Dayna Neo; Jean Clement; Minoru Takata; Shunichi Takeda; Julian Sale; Fred A Wright; James A Swenberg; et al. (PLoS ONE)
Contamination of potentially carcinogenic hexavalent chromium (Cr(VI)) in the drinking water is a major public health concern worldwide. However, little information is available regarding the biological effects of a nanomoler amount of Cr(VI). Here, we investigated the genotoxic effects of Cr(VI) at nanomoler levels and their repair pathways. We found that DNA damage response analyzed based on differential toxicity of isogenic cells deficient in various DNA repair proteins is observed after a three-day incubation with K2CrO4 in REV1-deficient DT40 cells at 19.2 μg/L or higher as well as in TK6 cells deficient in polymerase delta subunit 3 (POLD3) at 9.8 μg/L or higher. The genotoxicity of Cr(VI) decreased ~3000 times when the incubation time was reduced from three days to ten minutes. TK mutation rate also significantly decreased from 6 day to 1 day exposure to Cr(VI). The DNA damage response analysis suggest that DNA repair pathways, including the homologous recombination and REV1- and POLD3-mediated error-prone translesion synthesis pathways, are critical for the cells to tolerate to DNA damage caused by trace amount of Cr(VI).